Trichoderma Counteracts the Challenge of Phytophthora nicotianae Infections on Tomato by Modulating Plant Defense Mechanisms and the Expression of Crinkler, Necrosis-Inducing Phytophthora Protein 1, and Cellulose-Binding Elicitor Lectin Pathogenic Effectors - La Spada, Federico; Stracquadanio, Claudia; Riolo, Mario; Pane, Antonella; Cacciola, Santa Olga (Frontiers in Plant Science, 2020)
Decoding the mechanisms of plant defense against plant pathogens in a scenario where antagonistic activity and the plant growth promoting effects of useful organisms intervene simultaneously is a new frontier of Plant Pathology. Here we demonstrated that: (i) two selected strains of Trichoderma asperellum and T. atroviride promoted tomato (Solanum lycopersicum) growth and reduced the severity of disease caused by the oomycete Phytophthora nicotianae; (ii) the genetic patterns of the components of the experimental model system tomato - Trichoderma spp. - Phytophthora nicotianae were differentially expressed. The beneficial effects in both the promotion of the growth of host-plant and the biological control of the pathogen by two selected strains of different Trichoderma species were tested both in planta and in vitro. In both respects, T. atroviride demonstrated to be more effective than T. asperellum. Additionally, the simultaneous transcriptional reprogramming of several plant defense-related genes, pathogen effectors and mycoparasitism-related genes in tomato, P. nicotianae and Trichoderma spp., respectively was evaluated during the three-component interaction. Results support the hypothesis that Trichoderma spp. elicit the expression of plant-defense related genes. As expected, a mycoparasitism-related gene was significantly up-regulated in Trichoderma colonizing tomato plants infected by P. nicotianae. Finally, a marked up-regulation of the genes encoding two necrosis inducing effectors was observed in P. nicotianae infecting tomato plants colonized by Trichoderma. In conclusion, this study is a contribution towards understanding the genetic pathways related with the ability of Trichoderma spp. to counteract the challenge of P. nicotianae infections on tomato. Additionally, the experiments revealed the beneficial effects in the tomato growth promotion of a new Trichoderma atroviride strain and its good antagonistic effectiveness in the biological control of root and crown rot incited by P. nicotianae, confirming that Trichoderma spp. can be a powerful tool in integrated pest management strategies of Phytophthora diseases of horticultural crops.